The Effect of Implementing Problem-Based Learning based e-Worksheets Assisted by Flip PDF Corporate on Higher Order Thinking Skills - Mahyu, Ulfa Epriga; Distrik, I Wayan; Viyanti , Viyanti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to describe the effect of implementing problem-based learning-based e-worksheet assisted by flip PDF corporate on students' higher-order thinking skills (HOTs). Higher-order thinking skills in this study are measured using seven indicators: targeted thinking skills, theory formation, hypothesis formation, reasoning, analysis/evaluation, elaboration, and problem-solving. This digital-based learning innovation emerges as a response to the demands of the 21st century, which emphasize the importance of critical, analytical, and creative thinking skills in addressing real-world problems in daily life. The e-worksheet used not only presents learning materials in an interactive and engaging manner but is also designed to encourage students to explore concepts, connect knowledge, and solve context-based problems relevant to daily life. Additionally, the use of flip PDF corporate enables the presentation of materials in a more dynamic and easily accessible format via digital devices, thereby supporting flexibility in the teaching and learning process. This research was conducted at SMA Negeri 1 Kalianda in the even semester of the 2024/2025 academic year. The research sample consisted of two classes, namely grade XI Merdeka 6 as the experimental group and XI Merdeka 5 as the control group. The research method used was quasi-experimental with a non-equivalent control group design. The results of the study indicate that there is an effect of the implementation of e-worksheet based on problem-based learning assisted by flip PDF corporate on students' higher-order thinking skills. This is indicated by the average N-gain score for the experimental class of 0.67 in the moderate category and the control class of 0.29 in the low category. The results of the independent sample t-test showed a sig. (2-tailed) value under the assumption of equal variance of 0.00 < 0.05. Additionally, the results of the Effect Size test calculation showed a value of 2.24, categorized as high. These findings confirm that the integration of digital technology in the form of e-worksheet based on problem-based learning is not only capable of creating more engaging and interactive learning but also capable of optimizing students' cognitive potential. Therefore, it can be concluded that e-worksheet based on problem-based learning assisted by flip PDF corporate has a high influence in enhancing students' higher-order thinking skills.